ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI USAHA TANI JAGUNG DI KABUPATEN GROBOGAN TAHUN 2008 - Setiawan, Avi Budi; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2011)
Â Â Corn represents one of the agricultural comodities in Grobogan regency. However, the average corn production in Grobogan is only 4,92 ton/Ha. It is below the standard production determined by the government which ranges from 5,5 to 6 ton/ Ha. The aim of this study is to know the efficiency of production factors in farm bussiness, especially corn farm in Grobogan regency. The samples are 90 divisible respondents in Purwodadi, Torohand Kradenan. Then, the purposive cluster of area random sampling was applied for having the samples and quantitative descriptive approach was used for having the findings. After analyzing the data, it is shown that the variables influence the efficiency of production factors in farm bussiness are land area, seed production, and fertilizer production. Furthermore, those variables are inefficient in the busssiness farm. It is based on the calculation that shows the following findings: technical efficiency is 0,9996633, the price efficiency is1,53563, and the economic efficiency is 1,5346. Knowing that the variables involve in the farm bussiness, especially corn have not been efficient yet, the government roles are needed, and agriculture policy should be issued for protecting the peasants.